PENGARUH SPESIFIK KELIMPAHAN Avicennia marina TERHADAP KONSENTRASI KADMIUM (Cd) DALAM SEDIMEN DI WILAYAH PESISIR DEMAK - Hastuti, Endah Dwi (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2015)
The increasing stresses on mangrove ecosystem in Demak Municipal coastal area was caused by the high input of pollutant to the related ecosystem, including heavy metal as cadmium (Cd). In the other side, mangrove ecosystem also has the capacity in accumulating heavy metal so it doesn’t enter the marine waters. This research aimed to study the specific effect of Avicennia marina abundance on the accumulation of cadmium (Cd) concentration in mangrove sediment at Demak Municipal coastal area. This research was conducted through field observation by monitoring the abundance of Avicennia marina stands and accumulation of cadmium (Cd) concentration in Demak Municipal coastal area. The abundance of mangrove was specified on Avicennia marina tree stands, while concentration of cadmium (Cd) in sediment was achieved from field sampling. Data analysis was conducted through regression. The result showed the abundance of Avicennia marina stands was ranged from 2.200 – 6.200 stands/ha with average abundance of 4.028 ± 1.087 stands/ha, while concentration of cadmium (Cd) in mangrove ecosystem was ranged from 0,251 – 6,467 mg/kg with average of 2,828 ± 2,119 mg/kg. Analysis of regression showed there were significant effects of the Avicennia marina stands on the concentration of cadmium (Cd) in the mangrove sediments with the regression formula of Y = 7,294424 – 0,110888 X by probability level of 0,0138 (p < 0,05) and R2 = 0,3234. The abundance of Avicennia marina stands had negative effect on cadmium (Cd) concentration in mangrove sediments, since its capacity in absorbing and accumulation cadmium (Cd) in its organs. Keywords: Avicennia marina, cadmium, sediment, Demak